Prevalence of female sexual dysfunction among Indian fertile females - Vineet V Mishra; Sakshi Nanda; Bhumika Vyas; Rohina Aggarwal; Sumesh Choudhary; Suwa Ram Saini (Wolters Kluwer Medknow Publications, 2016)
Background: Female sexual dysfunction (FSD) is described as difficulty experienced by a female during any stage of a normal sexual activity including physical pleasure, desire, arousal, or orgasm. There are various factors responsible for FSD including psychological status of a person, gynecological or medical problems, long use of certain drugs, and social beliefs. Objectives: To study the prevalence and various factors associated with FSD. Materials and Methods: Study Design - This study design was a cross-sectional observational study conducted at Tertiary Care Centre, in Ahmedabad from June 2015 to March 2016. Sample Size - One hundred and fifty-three fertile females in reproductive age group (20-47 years) were included in the study. Written and informed consent was obtained from all the females. Methods - FSD was assessed with a detailed 19-item female sexual function index questionnaire. All six domains of sexual dysfunction, i.e., desire, arousal, lubrication, orgasm, satisfaction, and pain were studied. Various associated factors such as gynecological or psychological problems were also studied. Exclusion - Infertile patients were excluded from the study. Results: The prevalence of FSD was 55.55% among 153 fertile females. FSD was more prevalent in the age group of 26-30 years and with duration of marriage >16 years. FSD was also more common in females with middle education and those belonging to upper middle socioeconomic status. Psychological stress was significantly associated with FSD. Conclusion: It is right of every female to lead healthy sexual life as it is key to happiness in marriage. Females with FSD can be managed with proper counseling and treating the underlying etiology.